Closure of defects in a geometric figure pattern associated with tumescent anesthesia with lidocaine in rabbits (Oryctolagus cuniculus) - Serafim, Eduardo Luis [UNESP]; Pazzini, Josiane Morais [UNESP]; Rocha, Michelle do Carmo Pereira [UNESP]; Linhares, Lais Calazans Menescal [UNESP]; Nardi, Andrigo Barboza de [UNESP]; Gartner, Maria de Fatima Moutinho; Amorim, Irina; Rema, Alexandra; Faria, Fatima; Uscategui, Ricardo Andres Ramirez [UNESP]; Almeida, Vivian Tavares de [UNESP]; Calpaa, Carlos Alfredo; et al. (Univ Federal Goias, 2022)
The use of tumescent anesthesia with lidocaine can provide better intra-and postoperative analgesia that would benefit extensive reconstructive surgery. However, lidocaine can interfere with the healing process. Therefore, this study aimed to assess the local interference of the healing of induced and closed skin defects in a geometric pattern associated with the use of tumescent anesthesia with lidocaine in rabbits. Furthermore, we assessed its influence on cardiorespiratory parameters and postoperative analgesia. This study included 27 rabbits divided into three groups: GC (without the use of tumescence), GS (use of tumescence with 0.9% NaCl solution), and GL (use of tumescent anesthesia with lidocaine). There was no statistically significant intergroup difference in any stage of the wound healing process on macroscopic evaluations, in the angiogenesis process, or in the process of collagenization and fibroblast deposition. There were significant differences in heart rate (lower in GL), respiratory rate (higher in GC), mean arterial pressure (higher in GL), and expired concentration of isoflurane (lower in GL). There was no significant intergroup difference in the von Frey filament test or the visual analog scale score used to evaluate postoperative analgesia. We concluded that tumescent anesthesia with lidocaine does not impair postoperative tissue repair. Its use features benefits such as reducing the volume of inhaled anesthetic, maintaining the anesthesia plan, stable heart and respiratory rates, and lower hypotension during the surgical procedure.
Keywords: Local anesthetic; Pain; Reconstructive surgery; Tissue repair